A new three-dimensional vanadium selenite, (VO)(2)(SeO3)(3), with isolated and edge-shared VO6 octahedra - Halasyamani, P; O'Hare, D (1997)
Single crystals of (VO)2(SeO3)3 have been prepared from SeO2 and V2O5. The crystal structure has been determined by single-crystal X-ray diffraction. Crystal data: (VO)2(SeO3)3, Mr = 514.75; monoclinic, space group P21a (No. 14); cell parameters a = 9.151(1) Å, b = 6.353(1) Å, c = 14.992(1)Å, β = 93.538(5)°, and Z = 4. The structure consists of VO6 octahedra and SeO3 groups. The vanadium octahedra either are edge-sharing and form [V2O6.66]3.33- groups or are corner-linked through an [SeO3/2]+ cation. The structure may be rationalized in terms of connecting layers of {2[SeO2/2O1/3]4/3+[VO1/1O 4/2O1/3]5/3-}+ cations and {[SeO3/2]+[VO1/1O5/2]2-}- anions. © 1997 American Chemical Society.